Competitive advantage: Empirical evidence from the small business of culinary - Wan Suryani; Marissa Claudya (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2020)
The purpose of this study is to examine the characteristics of the current competitiveness of small culinary businesses, especially in the implementation of entrepreneurial marketing and innovation. This study used a sample of 80 small culinary businesses in Medan City, Indonesia. The analysis using the partial least square method was used to test the constructed model that was built. The results of this study indicate that small culinary businesses organically understand and feel the benefits of entrepreneurial marketing and innovation in increasing competitiveness. However, the impact can still be accelerated by improvements through the intervention of policymakers.